2013
DOI: 10.1080/17487870.2013.799916
|View full text |Cite
|
Sign up to set email alerts
|

The relation between capital formation and economic growth: evidence from sub-Saharan African countries

Abstract: This paper examines the causal relationship between capital formation and economic growth in Sub-Saharan African countries using recent panel cointegration and causality testing techniques. We find that causality is bi-directional, suggesting that higher economic growth leads to higher capital formation and that in turn, increases in capital formation results in higher economic growth. These results hold irrespective of whether capital formation is measured with private fixed capital formation or by gross capi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 30 publications
12
24
0
Order By: Relevance
“…Similarly, positive impact of gross fixed capital formation is harmonized with model of Harrod (1939) and Domar (1946), jointly called Harrod-Domar growth model. These are similar to the findings of Hassan, Sanchez, andYu (2011), Ali, Chaudhry, andFarooq (2012), Uneze (2013). The effect of government consumption and population growth is, however, negative and significant.…”
Section: Resultssupporting
confidence: 88%
“…Similarly, positive impact of gross fixed capital formation is harmonized with model of Harrod (1939) and Domar (1946), jointly called Harrod-Domar growth model. These are similar to the findings of Hassan, Sanchez, andYu (2011), Ali, Chaudhry, andFarooq (2012), Uneze (2013). The effect of government consumption and population growth is, however, negative and significant.…”
Section: Resultssupporting
confidence: 88%
“…Similarly, bi-directional causal link has been found between capital accumulation and economic growth in developed countries. This finding is consistent with Ahmed et al (2016), Narayan and Smyth (2008), Neanywa and Makhenyane (2016), Satti et al (2014), Onyinye et al (2017) and Topcu et al (2020), Uneze (2013) . In developed countries, there is bi-directional causality between labour and economic growth.…”
Section: Discussionsupporting
confidence: 90%
“…Gibescu (2010) concluded that there exists a strong relationship between GFCF and GDP growth. Uneze (2013) stated that causality between gross fixed capital formation and economic growth is bi-directional. This means that increasing capital formation boosts economic growth or that higher economic growth results in higher capital formation.…”
Section: B Literature Reviewmentioning
confidence: 99%